Gonadal bacterial community composition is associated with sex-specific differences in swamp eels (Monopterus albus) - Meng, Kaifeng; Lin, Xing; Liu, Hairong; Chen, Huijie; Liu, Fei; Xu, Zhen; Sun, Yonghua; Luo, Daji (Frontiers in Immunology, 2022)
Organisms are colonized by microorganism communities and play a pivotal role in host function by influencing physiology and development. In mammals, bacterial community may alter gonadal maturation and drive sex-specific differences in gene expression and metabolism. However, bacterial microbiota diversity in the gonads of early vertebrates has not been fully elucidated. Here, we focused on the swamp eel (Monopterus albus), which naturally undergoes sex reversal, and systematically analyzed the bacterial microbiota profiles between females and males using 16S rRNA gene sequences. Specifically, the microbial abundance and community diversity of gonads in males were higher than in females. Although Proteobacteria, Firmicutes, Bacteroidetes, and Actinobacteria were characterized as the dominating phyla in ovary and testis, the relative abundance of Firmicutes was significantly higher in males than females. Detailed analysis of the microbial community revealed that Bacilli were the dominant bacteria in ovaries and Clostridium in testes of M. albus. More importantly, we proposed that differences in the microbial composition and distribution between ovaries and testes may be linked to functional categories in M. albus, especially metabolism. These findings represent a unique resource of bacterial community in gonads to facilitate future research about the mechanism of how microbiota influence sex-specific differences and sex reversal in vertebrates.